Equity market conditions and profitability of momentum long-short arbitrages in the U.S.A. REITs Market : 1972-2008. - Lee, Milene Yen Yen. (2009)
Motivated by an earlier study on {6,6} momentum profitability of U.S.A. REITs for the 1972 – 2000 sample period, this report has reexamined the momentum profits for the extended sample period from 1972 to 2008 and for both {3,3} and {6,6} strategies. Our main finding indicates that the earlier existence of significant momentum profits for {6,6} strategy also held for the extended period and for {3,3} strategy. Three other main findings were: (1) the momentum returns that were higher in up markets for the 1972 – 2000 period became significantly lower for the 2001 – 2008 period; (2) the momentum returns decreased after the 1992 regulatory changes in the REITs industry and decreased significantly further after the 2000 property market boom in the U.S.A.; and (3) the momentum returns that were explained by the REITs’ dividend growth rates (proxied by the REITs’ dividend/price ratios in the earlier study) were not similarly explained for the 2001 – 2008 period.